TIGIT as a Promising Therapeutic Target in Autoimmune Diseases - Yue, Chenran; Gao, Sheng; Li, Shuting; Xing, Zhouhang; Qian, Hengrong; Hu, Ying; Wang, Wenqian; Hua, Chunyan (Frontiers in Immunology, 2022)
Co-inhibitory receptors (IRs) are molecules that protect host against autoimmune reactions and maintain peripheral self-tolerance, playing an essential role in maintaining immune homeostasis. In view of the substantial clinical progress of negative immune checkpoint blockade in cancer treatment, the role of IRs in autoimmune diseases is also obvious. Several advances highlight the substantial impact of T cell immunoglobulin and ITIM domain (TIGIT), a novel IR, in autoimmunity. Blockade of TIGIT pathway exacerbates multiple autoimmune diseases, whereas enhancement of TIGIT function has been shown to alleviate autoimmune settings in mice. These data suggest that TIGIT pathway can be manipulated to achieve durable tolerance to treat autoimmune disorders. In this review, we provide an overview of characteristics of TIGIT and its role in autoimmunity. We then discuss recent approaches and future directions to leverage our knowledge of TIGIT as therapeutic target in autoimmune diseases.